2021
DOI: 10.1021/acs.jafc.1c02434
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolic Analysis of Fruit Development and Identification of Genes Involved in Raffinose and Hydrolysable Tannin Biosynthesis in Walnuts

Abstract: Walnut (Juglans regia L.) is an important fruit tree with high nutrition in its nuts. Here, the development of walnut fruits was monitored, and nine biological samples at five developmental stages were collected and analyzed by transcriptomic and metabolic assays. Many phenolic metabolites accumulated in the peel of mature fruits, while lipids, carbohydrates, and amino acids and their derivatives mainly accumulated in the kernel. Fatty acid biosynthesis occurred at 13 weeks after pollination, and photosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…The following antibodies were used: Novogene Co., Ltd. (Beijing, China). All parameters and conditions were set the same as those used in a previous study (35), and the raw data generated by the LC-MS/MS system were analyzed using the software SCIEX OS Version 1.4 to integrate and correct the chromatographic peak. All metabolomics data were analyzed by the website-based tool MetaboAnalyst (http://www.metaboanalyst.ca).…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…The following antibodies were used: Novogene Co., Ltd. (Beijing, China). All parameters and conditions were set the same as those used in a previous study (35), and the raw data generated by the LC-MS/MS system were analyzed using the software SCIEX OS Version 1.4 to integrate and correct the chromatographic peak. All metabolomics data were analyzed by the website-based tool MetaboAnalyst (http://www.metaboanalyst.ca).…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…In addition, 15 DAMs belonged to flavonoid and flavonol biosynthesis ( Figure S2 ), of which 13 metabolites accumulated in greater quantities in the endopleura than that in the embryo. This result was similar to the study of Wang et al [ 20 ].…”
Section: Resultssupporting
confidence: 93%
“…A total of 120 metabolites were initially identified, including hydrolyzed and condensed tannins, flavonoids, and phenolic acids. Wang et al [ 20 ] reported that many phenolic metabolites accumulate in the endopleura of mature fruits, while lipids and amino acids and their derivatives mainly accumulate in the embryo. However, the reasons for high polyphenol content in walnut endopleura have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The combined analysis with transcriptome data demonstrates that the Asr1 [i.e., abscisic acid (ABA), stress, and ripening 1] transcription factor is involved in the cascade regulation of red tomato fruit maturation (Dominguez et al, 2021). Special metabolites also accumulate in mangosteen (Mamat et al, 2020), ginseng berry (Park et al, 2019), starfruit (Ramadan et al, 2020), avocado (Hurtado-Fernández et al, 2015), strawberry (Zhang et al, 2011;Wang et al, 2021e), apple (Rudell and Mattheis, 2009;Risticevic et al, 2016Risticevic et al, , 2020Jing and Malladi, 2020;Xu et al, 2020), grape berry (Dai et al, 2013), mulberry (Lee et al, 2016), cupressaceae (Falasca et al, 2014), olea (Olmo-García et al, 2018), walnuts (Wang et al, 2021b), and African baobab (Baky et al, 2021) during fruit maturing.…”
Section: Fruit Quality Formationmentioning
confidence: 99%